Pd-Catalyzed Intermolecular Dehydrogenative Heck Reactions of Five-Membered Heteroarenes - Le Bras, Jean; Muzart, Jacques (Catalysts, 2020)
The Pd-mediated cross-coupling of (hetero)arenes with alkenes may be an effective method for the formation of a C–C bond from two C–H bonds. Discovered by Fujiwara and co-workers in 1967, this reaction led to a number of reports that we firstly highlighted in 2011 (review with references till June 2010) and for which, we retained the name “dehydrogenative Heck reaction”. The topic, especially the reactions of five-membered heteroarenes, has been the subject of intensive research over the last ten years. The present review is limited to these dehydrogenative Heck reactions published since 2010, underlining the progress of the procedures.